(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The influences of adding pure ethanol 99.9% (0E, 10E, 20E, 30E, 40E, 50E,) to gasoline 750 blends on the performance of the engine and characteristic emission of spark ignition (SI) engine are conducted in the present study. The Internal combustion engine that employed in the experiment has specifications of a (singl – cylinder) and 4- stroke (SI). Performance tests are carried out for brake power (Bp), brake specific fuel consumption (Bsfc), brake thermal efficiency (ηBth), for carbon dioxide (CO2), carbon-monoxide (CO) and hydrocarbon born (HC) emissions. The measurements are recorded under several engine speeds from (1500-2500rpm) for two cases, the first with load and the second case without load. The experimental result showed that ethanol- gasoline750 blends fuel increases the (Bp), and (ηBth) about 2.61% and 30.9%, respectively for all engine speeds. Also, the (Bsfc) a bit decreases about 4.97%. By increasing the ethanol- gasoline750 blend fuel decreases the CO, HC emissions about 4.67% and 6.4%, respectively, where the CO2 concentration increases about 6.1%. It was detected that the temperature of exhaust gas increases about 33.60%, as engine speed increases